EVALUATION OF NODULE AND NITROGEN PRODUCTION PERFORMANCE OF Vicia faba L. VARIETIES ON SOIL FERTILITY IN HADIYA ZONE, SOUTHERN ETHIOPIA - MADOLO, MULATU CHERNET (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Nitrogen-fixing legumes are an essential component of healthy soil for long-term crop Reduced soil fertility and deterioration of agricultural production potential are major impediments to poverty alleviation in many impoverished areas. Nitrogen-fixing legumes are an important part of a healthy soil for long-term crop production systems. To improve soil fertility, an experiment was carried out to evaluate the nodulation and N fixation potential of faba bean variety legumes grown in two districts. Six composite soil samples were collected from each site at depths ranging from 0 to 30 cm. The soil samples were taken from fields that were known to grow continuous cereal crops. As a result, the experiment was carried out in the RCBD under field conditions, with three field replication soils. Before and after sowing, soil parameters were investigated. The effect of two district levels revealed that soil properties prior to planting were significant (P<0.05) for all parameters investigated. Nodule, atmospheric nitrogen, nodule color inside soil N and N, and plant dry matter content were measured for Hachalu and Dosha. The study revealed a significant value (P<0.05), and Hachalu had a higher value for the parameters studied under Duna soil than Dosha with the same parameters. Similarly, Dosha recorded higher values for the parameters studied in Lemo District soils than in Hachalu soils. As a result of this research, we can conclude that growing Hachalu on the Duna District soil and Dosha on the Lemo District soil would improve soil fertility quickly and inexpensively, thereby increasing crop productivity.